Exercise-Induced Cardiac Troponin I Increase and Incident Mortality and Cardiovascular Events. Issue 10 (3rd September 2019) - Aengevaeren, Vincent L.; Hopman, Maria T.E.; Thompson, Paul D.; Bakker, Esmée A.; George, Keith P.; Thijssen, Dick H.J.; Eijsvogels, Thijs M.H.
Abstract : Background: Blood concentrations of cardiac troponin above the 99 th percentile are a key criterion for the diagnosis of acute myocardial injury and infarction. Troponin concentrations, even below the 99 th percentile, predict adverse outcomes in patients and the general population. Elevated troponin concentrations are commonly observed after endurance exercise, but the clinical significance of this increase is unknown. We examined the association between postexercise troponin I concentrations and clinical outcomes in long-distance walkers. Methods: We measured cardiac troponin I concentrations in 725 participants (61 [54–69] yrs) before and immediately after 30 to 55 km of walking. We tested for an association between postexercise troponin I concentrations above the 99 th percentile (>0.040 µg/L) and a composite end point of all-cause mortality and major adverse cardiovascular events (myocardial infarction, stroke, heart failure, revascularization, or sudden cardiac arrest). Continuous variables were reported as mean ± standard deviation when normally distributed or median [interquartile range] when not normally distributed. Results: Participants walked 8.3 [7.3–9.3] hours at 68±10% of their maximum heart rate. Baseline troponin I concentrations were >0.040 µg/L in 9 participants (1%). Troponin I concentrations increased after walking ( P <.001), with 63 participants (9%) demonstrating a postexercise troponin concentration >0.040 µg/L. During 43 [23–77] months of follow-up, 62 participants (9%) experienced an end point; 29 died and 33 had major adverse cardiovascular events. Compared with 7% with postexercise troponin I ⩽0.040 µg/L (log-rank P <.001), 27% of participants with postexercise troponin I concentrations >0.040 µg/L experienced an end point. The hazard ratio was 2.48 (95% CI, 1.29–4.78) after adjusting for age, sex, cardiovascular risk factors (hypertension, hypercholesterolemia or diabetes mellitus), cardiovascular diseases (myocardial infarction, stroke, or heart failure), and baseline troponin I concentrations. Conclusions: Exercise-induced troponin I elevations above the 99 th percentile after 30 to 55 km of walking independently predicted higher mortality and cardiovascular events in a cohort of older long-distance walkers. Exercise-induced increases in troponin may not be a benign physiological response to exercise, but an early marker of future mortality and cardiovascular events. Abstract : Supplemental Digital Content is available in the text.